The discursive production of professionals about humanizing health: singularity, rights and ethics - Rose Mary Costa Rosa Andrade Silva; Denize Cristina de Oliveira; Eliane Ramos Pereira (Universidade de São Paulo, 2015)
Objective: to describe the discursive production of professionals about the humanization of health.Method: qualitative study of descriptive approach, inspired by the social representation theory, with 24 professionals in the healthcare field, working in a university hospital with the established humanization policy. The selection of participants was conducted according to criteria of adequacy and diversity for an intentional sample. Data collection was conducted by semi-structured interviews.Results: through content analysis, three categories emerged, around which the analyses were conducted: "humanizing health as an act of accepting the other as unique", "humanizing health as a matter of right" and "humanizing health as an ethical issue". The discursive production of professionals is based on a perspective which is based on the humanist prospect with socio-historical bias.Conclusion: healthcare professionals must know the National Humanization Policy in order to provide quality care, promoting the meeting, welcoming and recognition of oneself, others and their profession in the political and socio-historical scenario of their country as a citizen, not only of rights, but also of obligations.